Digital anthropometry for body circumference measurements: Toward the development of universal three‐dimensional optical system analysis software - Sima Sobhiyeh; Samantha Kennedy; Alexander Dunkel; Marcelline E. Dechenaud; Jerome A. Weston; John Shepherd; Peter Wolenski; Steven B. Heymsfield (Wiley, 2021)
Abstract Background/Objective Digital anthropometric (DA) assessments are increasingly being administered with three‐dimensional (3D) optical devices in clinical settings that manage patients with obesity and related metabolic disorders. However, anatomic measurement sites are not standardized across manufacturers, precluding use of published reference values and pooling of data across research centers. Subjects/Methods This study aimed to develop universal 3D analysis software by applying novel programming strategies capable of producing device‐independent DA estimates that agree with conventional anthropometric (CA) measurements made at well‐defined anatomic sites. A series of technical issues related to proprietary methods of 3D geometrical reconstruction and image analysis were addressed in developing major software components. To evaluate software accuracy, comparisons were made to CA circumference measurements made with a flexible tape at eleven standard anatomic sites in up to 35 adults scanned with three different commercial 3D optical devices. Results Overall, group mean CA and DA values across the three systems were in good agreement, with ∼2 cm systematic differences; CA and DA estimates were highly correlated (all p‐values <0.01); root‐mean square errors were low (0.51-3.27 cm); and CA‐DA bias tended to be small, but significant depending on anatomic site and device. Conclusions Availability of this software, with future refinements, has the potential to facilitate clinical applications and creation of large pooled uniform anthropometric databases.